Profil Berpikir Kreatif Mahasiswa dalam Memecahkan Masalah Sistem Persamaan Linier Berbasis Kontekstual Ditinjau dari Kecerdasan Matematika Logis - Restu Lusiana (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2017)
This research is meant to understand the thinking profile of students in solving the system linear problem seen from mathematical logic intelligence. This is descriptive qualitative research. The data collection technique used in this research are test and interview. The data validation method is done through triangulation method. The data analysis method is done through data reduction, data presentation and data verification. The subject used in this research is selected through mathematical logic intelligence test score of first semester students from Information Technique Department. Based on the test score of mathematical logic intelligence, the researcher selected three subjects which is then categorized into three categories namely, high, medium and low. The conclusion of this research are: 1) student with high mathematical logic intelligence in the stage of finding and writing all information, in incubation stage, student can solve problem through varied solution methods, in the insight stage, student can understand the problem well by coming to the same answer through varied methods, 2) student with medium mathematical logic intelligence solved the problem at the stage of finding information needed, in incubation stage by choosing different method from what is taught, at the insight stage, student can find the result through his own method, 3) student with low mathematical logic intelligence at the preparation stage can find all information needed, at the incubation stage, student tried varied methods, but until insight stage.